Stress ulcer prophylaxis in the intensive care unit trial: detailed statistical analysis plan. Issue 7 (12th June 2017) - Krag, M.; Perner, A.; Wetterslev, J.; Lange, T.; Wise, M. P.; Borthwick, M.; Bendel, S.; Pelosi, P.; Keus, F.; Guttormsen, A. B.; Schefold, J. C.; Meyhoff, T. S.; et al.
Abstract : Background: In this statistical analysis plan, we aim to provide details of the pre‐defined statistical analyses of the Stress Ulcer Prophylaxis in the Intensive Care Unit (SUP‐ICU) trial. The aim of the SUP‐ICU trial is to assess benefits and harms of stress ulcer prophylaxis with a proton pump inhibitor in adult patients in the intensive care unit (ICU). Methods: The SUP‐ICU trial is an investigator‐initiated, international, multicentre, randomised, blinded, parallel‐group trial of intravenously pantoprazole 40 mg once daily vs. placebo in 3350 acutely ill adult ICU patients at risk of gastrointestinal bleeding. The primary outcome measure is 90‐day mortality. Secondary outcomes include the proportion of patients with clinically important gastrointestinal bleeding, pneumonia, Clostridium difficile infection or myocardial ischaemia, days alive without life support, serious adverse reactions, 1‐year mortality, and a health economic analysis. Two formal interim analyses will be performed. The statistical analyses will be conducted according to the outlined pre‐defined statistical analysis plan. The primary analysis will be a logistic regression analysis adjusted for stratification variables comparing the two intervention groups in the intention‐to‐treat population. In a secondary analysis, we will additionally adjust the primary outcome for potential random differences in baseline characteristics. The conclusion will be based on the intention‐to‐treat population. Conclusion: Stress ulcer prophylaxis is standard of care in ICUs worldwide, but has never been tested in large high‐quality randomised placebo‐controlled trials. The SUP‐ICU trial will provide important high‐quality data on the balance between the benefits and harms of stress ulcer prophylaxis in adult critically ill patients.